Role of Steroid Hormone Receptors in Formation and Progression of Bladder Carcinoma: A Case-Control Study - Mashhadi, Rahil; Pourmand, Gholamreza; Kosari, Farid; Mehrsai, Abdolrasoul; Salem, Sepehr; Pourmand, Mohammad Reza; Alatab, Sudabeh; Khonsari, Mehdi; Heydari, Fariba; Beladi, Laleh; Alizadeh, Farimah (Urology Journal, 2014)
Purpose: To compare the expression rate of sex steroid hormone receptors of estrogen (ER), progesterone (PR) and androgen (AR) in normal urothelium and urothelial bladder cancer (UBC) and to evaluate the possible associations of these receptors expression with cancer progression and patient's survival. Materials and Methods: We evaluated the clinical data and tumor specimens of 120 patients with pathologically confirmed primary UBC with 132 normal healthy controls. Both patients and controls selected from list of subjects who have been referred to Sina Urology clinic, and had a minimum of one year follow-up duration. Data collected from medical cords. For evaluation of expression, immunohistochemistry was performed on paraffin-embedded tissue sections using a monoclonal antibody for androgen, estrogen and progesterone receptors. Presence of at least 10% positive cells defined as positive expression. Results: None of the control subjects showed AR expression, while 22% of the patients were AR-positive. ER/PR expressions were observed in 4.2%/ and 2.5% of the cases and in 2.3% and 1.5% of the controls, respectively. A statistically significant correlation was found between AR expression and tumor stage and grade (P < .001). AR-positive patients showed a significantly poorer prognosis than AR-negative cases (log-rank test, P = .02, hazard ratio = 2.12; 95% confidence interval: 1.36-4.65). Conclusion: AR expression was significantly associated with higher grade and poorly differentiated tumors with unfavorable outcome. AR expression test might be useful as a diagnostic tool for determining the malignancy and outcome of UBC patients.